2022
DOI: 10.30935/scimath/12339
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Method Approach to Investigate the Effect of Flipped Inquiry-Based Learning on Chemistry Students Learning

Abstract: This study investigated the effects of flipped inquiry-based learning approach (FIBL) on chemistry students' academic performance and learning experiences. This study utilized a mixed research methods approach with a quasi-experimental design. A convenient sampling technique was used to identify pre-service teachers studying chemistry at the college of education in Ghana. Quantitative data was obtained using a chemistry academic achievement test and critical thinking skills test. Qualitative data was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For instance, Laursen et al [21] concluded that PBL is an effective instructional approach for supporting student teachers attitudes towards group work to discover ideas for understanding mathematics concepts. Some studies have indicated that PBL improves student teachers critical thinking skills [24][25][26]. For instance, Aidoo et al [24] showed that PBL enhances student teachers motivation to develop critical thinking skills to understand and apply their knowledge into practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Laursen et al [21] concluded that PBL is an effective instructional approach for supporting student teachers attitudes towards group work to discover ideas for understanding mathematics concepts. Some studies have indicated that PBL improves student teachers critical thinking skills [24][25][26]. For instance, Aidoo et al [24] showed that PBL enhances student teachers motivation to develop critical thinking skills to understand and apply their knowledge into practice.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that PBL improves student teachers critical thinking skills [24][25][26]. For instance, Aidoo et al [24] showed that PBL enhances student teachers motivation to develop critical thinking skills to understand and apply their knowledge into practice. In other research, many studies have reported that PBL improves student teachers academic performance [24,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, checking conclusions might improve student correlational skills. The IBL is an effective pedagogical approach where students can develop knowledge and thinking skills [77].…”
Section: Discussionmentioning
confidence: 99%
“…Teaching science can have a positive impact on students, particularly when conducted within the framework of inquiry-based learning, ensuring active participation rather than passive observation [32][33][34]. The utilization of Arduino in this context has become increasingly prevalent in recent times.…”
Section: Arduino In Educationmentioning
confidence: 99%